Genome mining and functional analysis of cytochrome P450 genes involved in insecticide resistance in Leucinodes orbonalis (Lepidoptera: Crambidae). (23rd September 2020) - Kariyanna, Bheeranna; Prabhuraj, Aralimarad; Asokan, Ramasamy; Ramkumar, Govindaraju; Venkatesan, Thiruvengadam; Gracy, Ramasamy G.; Mohan, Muthugounder
Abstract: Genome‐wide analysis of cytochrome P450 monooxygenase (CYP) genes from the advanced genome project of the Leucinodes orbonalis and the expression analysis provided significant information about the metabolism‐mediated insecticide resistance. A total of 72 putative CYP genes were identified from the genome and transcriptome of L. orbonalis . The genes were classified under 30 families and 46 subfamilies based on the standard nomenclature. In the present study, a novel CYP gene, CYP324F1, was identified and it has not been reported from any other living system so far. Biochemical assays showed enhanced titers (5.81–18.5‐fold) of O‐demethylase of CYP in five field‐collected populations. We selected 34 homologous CYP gene sequences, seemed to be involved in insecticide resistance for primer design and quantitative real‐time PCR studies. Among the many overexpressed genes (>10 fold), the expression levels of CYP324F1 and C YP306A1 were prominent across all the field populations as compared with the susceptible iso‐female line. Oral delivery of ds‐ CYP324F1 and ds‐C YP306A1 directed against CYP324F1 and C YP306A1 to the larvae of one of the insecticide resistance populations caused reduced expression of these two transcripts in a dose‐dependent manner (53.4%–85.0%). It appears that the increased titer of O‐demethylase is the result of increased transcription level of CYP genes in resistant populations. The data provide insight for identifying the novel resistance management strategies against L. orbonalis . Abstract : Functional validation of highly expressed CYP450 gene of L. orbonalis by dsRNA based gene silencing